Osteoporosis in brazilian patients awaiting knee arthroplasty - David Sadigursky; Luiz Alberto Barretto Junior; Diogo Maciel Vieira Lobão; Rogério Jamil Fernandes Carneiro; Paulo Oliveira Colavolpe (Acta Ortopédica Brasileira, 2017)
ABSTRACT OBJECTIVE: The primary objective of this study was to determine the prevalence of osteoporosis and osteopenia prior to total knee arthroplasty (TKA) in female patients. As a secondary objective, we evaluated the incidence of hip fractures, types of drugs to treat osteoporosis and serum vitamin D levels. METHOD: This is a transversal, descriptive and observational study which evaluated 60 women above age 55 prior to total knee replacement. RESULTS: Mean patient age was 71.4 years. Osteoporosis was present in 16.7% of the sample and osteopenia in 15%. In the patients with osteoporosis, femur fracture (20%) was most frequent. Most of the group with osteopenia did not take any medication to treat this condition (55.6%), while most patients with osteoporosis took alendronate (30%) and 30% did not take any medication. CONCLUSION: The female population awaiting total knee replacement should be considered at risk for osteoporosis, confirming recent findings in the literature. Level of Evidence III, Control Case Study.